1997
DOI: 10.2307/3237369
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in nutrient concentration in leaves and branches of Quercus pyrenaica

Abstract: Abstract. Seasonal variation in nutrient concentration in leaves and branches of Quercus pyrenaica was studied in natural Q. pyrenaica forest in the Sierra de Gata (Salamanca Province, Spain). Two permanent plots were established at the two extremes of a rainfall gradient in this area: annual mean precipitation from 720 mm at Fuenteguinaldo (granite bedrock) to 1580 mm at Navasfrias (schists and graywackes). Leaf and branch samples were collected every three weeks during the growing season from May to October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Considering the time frame of sample collection (i.e. end of the growing season), the results obtained in this study are in accordance with the findings of Santa Regina et al [24]. Namely, the authors continually reported seasonal accumulation of these two elements in the leaves of Quercus pyrenaica, whereas only slight increase in accumulation, but not statistically significant, was observed to have occurred in the branches.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Considering the time frame of sample collection (i.e. end of the growing season), the results obtained in this study are in accordance with the findings of Santa Regina et al [24]. Namely, the authors continually reported seasonal accumulation of these two elements in the leaves of Quercus pyrenaica, whereas only slight increase in accumulation, but not statistically significant, was observed to have occurred in the branches.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies demonstrated that HMs content within Quercus genus is species-and organ-dependent [22,23], although environmental conditions [5] and tree lifetime have certain effects on HMs accumulation as well [24]. Since HMs content in two oak species occurring at separated sites and, therefore, growing under different environmental conditions was examined, direct comparison of absolute values of HMs content in their organs was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…The high nitrogen demands of deciduousness, the low average nitrogen availability, and the seasonal pattern of nitrogen and water availability in the study system imply that nitrogen conservation may be important. Deciduous trees can conserve nitrogen through nutrient resorption or the withdrawal of nutrients from senescing leaves and the storage of these nutrients in woody parts [ 20 23 ]. Many savanna trees deploy new leaves, just before the rains, using these stored resources [ 24 – 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang's experiments in Karst regions (Zhang et al, 2015) and several other studies (Davidson et al, 2007;Du, Pan, Li, Hu, & Wang, 2011;Huang et al, 2013) have indicated that foliar N:P ratios may change with succession owing to the N cycling properties recover accompanying with P limitation increases in mature forests. The stoichiometric ratios may also vary seasonally, because nutrient concentrations in leaves change with phenology, particularly in deciduous species (Regina, Rico, Rapp, & Gallego, 1997;Robert, Caritat, Bertoni, Vilar, & Molinas, 1996). However, published literatures focus more on stoichiometric change patterns on a large scale, such as in the world's temperate forests or tropical rain forests He et al, 2006He et al, , 2008McGroddy et al, 2004;Reich & Oleksyn, 2004), whereas research on stoichiometry variations with seasons and successions among different tree species in individual forest or on a small scale is less developed.…”
mentioning
confidence: 99%